Studies of the atmospheric muon flux with the ANTARES detector - Bazzotti, Marco <1980> (Alma Mater Studiorum - Università di Bologna, 2009)
The thesis main topic is the determination of the vertical component of the atmospheric muon flux as a function of the sea depth at the ANTARES site. ANTARES is a Cherenkov neutrino telescope placed at 2500m depth in the Mediterranean Sea at 40 km from the southern cost of France. In order to retrieve back the physical flux from the experimental data a deconvolution algorithm has been perform which takes into consideration the trigger inefficiensies and the reconstruction errors on the zenith angle. The obtained results are in good agreement with other ANTARES indipendent analysis.